The Palaearctic types of Chrysididae (Insecta, Hymenoptera) deposited in the Linsenmaier collection. Part 5. Elampini: genus Holopyga Dahlbom, 1845 - Rosa, Paolo; Felsner, Christian; Heim, René; Greeff, Michael; Michez, Denis; Bernasconi, Marco Valerio (Zootaxa, 2025)
An illustrated catalogue of the Palaearctic types of species and subspecies of Holopyga Dahlbom, 1845 described by Walter Linsenmaier is presented. Linsenmaier described 48 species and subspecies of Holopyga and most of the primary types are deposited in the collection of the Natur-Museum in Luzern, Switzerland, with the exception of five holotypes which are deposited in other public and private collections. This catalogue includes the list of the described species, photographs of 41 holotypes and a synthesis of the recent changes in the taxonomy of Holopyga to update Linsenmaier’s classification. New synonymies are proposed for the subgenus Chamaeholopyga Linsenmaier, 1987 syn. nov. of Pseudolopyga Krombein, 1969 and for two species: Holopyga unitasculpta Linsenmaier, 1968 syn. nov. of H. solskyi (Radoszkowski, 1877) and H. jurinei Chevrier, 1862 syn. nov. of H. lucida (Lepeletier, 1806). Additionally, a new species, Holopyga dichroica Rosa sp. nov., formally referred to as H. jurinei sensu Linsenmaier 1959a is described.